+0  
 
0
218
1
avatar

https://prnt.sc/ovabki

 

thank you 

 Aug 20, 2019
 #1
avatar+111325 
+1

3x + 4

___________         we can solve this with partial fractions

x^2 -6x + 5

 

 

3x + 4                                 A              B

___________   =            _____  +    ____           multiply through by  (x -5) ( x - 1)

(x - 5) ( x - 1)                    x - 1          x - 5

 

 

3x + 4   = A(x - 5)  + B ( x - 1)

 

3x + 4  =  Ax - 5A  + Bx - B        

 

3x + 4  =  (A + B) x  -  (5A + 5B)        equate coefficients

 

A + B  =  3

 

-5A - B = 4        add these equations

 

 

-4A  = 7     

 

A =  -7/4

 

And   

 (-7/4) + B  =  3

-7/4 + B = 12/4

B  = 19/4

 

 

So   the solution  is

 

3x+4                           - 7                      19

__________     =    _________  +  ________

x^2 - 6x + 5               4 ( x - 1)          4 (x - 5)

 

 

cool cool cool

 Aug 21, 2019

18 Online Users

avatar
avatar
avatar
avatar
avatar